Effectiveness of antioxidants on in vitro regeneration of Musa paradisiaca var. raja to prevent browning and enhance embryo development - Aisiyya Qutlana Munawaroh, Putri; Pancaningtyas, Sulistyani; Su'udi, Mukhamad (Indonesian Coffee and Cocoa Research Institute, 2024)
The cultivation of raja banana is widespread in Indonesia. The process of increasing banana propagation through in vitro culture encounters a specific issue, namely the occurrence of browning during the initiation stage, which hinders the regeneration process. The objective of this study is to determine the effectivenessof antioxidants on the in vitro regeneration of raja banana to prevent browning and enhance embryo development. The study was conducted using a completely randomized design with the treatment of the antioxidant compounds ascorbic acid (AS) and melatonin (MN). The treatments consisted of control (without antioxidants), ascorbic acid (100 mg L-1, 150 mg L-1, and 200 mg L-1) and melatonin (10 mg L-1, 12 mg L-1, and 14 mg L-1). The results showed that ascorbic acid and melatonin treatment had no significant effect on the percentage of viable explants and the level of browning intensity, but provided significant results on the regeneration process. The application of melatonin at 14 mg L-1 significantly increased callus regeneration. Furthermore, at a concentration of 12 mg L-1 showed the highest callus percentage value compared to other treatments. The melatonin 12 mg L-1 treatment showed the earliest scutellar embryo formation, whereas ascorbic acid at a concentration of 100 mg L-1 resulted in the most optimal regeneration of globular and scutellar embryos. The highest concentrations of ascorbic acid and melatonin inhibit the formation of coleoptilar embryos